2011
DOI: 10.1016/j.jtcvs.2010.08.061
|View full text |Cite
|
Sign up to set email alerts
|

Continued depression of maximal oxygen consumption and mitochondrial proteomic expression despite successful coronary artery bypass grafting in a swine model of hibernation

Abstract: Despite successful revascularization of hibernating myocardium, regional function and blood flow remained depressed during catecholamine stress. Electron transport chain proteins known to be downregulated during adaptive process within hibernating myocardium did not normalize after revascularization. These data demonstrate a potential bioenergetic cause of persistent dysfunction and heart failure within successfully revascularized hibernating myocardium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
52
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 26 publications
5
52
1
Order By: Relevance
“…This study is to our knowledge the first to report such data in paired biopsies from human heart, and the results are in agreement with previous observations of decreased OXPHOS capacity in chronic cardiac ischemia in animal models (4,12,16,17). The composition of the present substrate-inhibitor protocol was done with a stepwise addition of substrates: first for complex I linked respiration and then for combined complex-I and -II respiration, followed by inhibition of complex I, leaving only complex II-linked respiration, and finally inhibition of the entire respiratory chain respiration by antimycin A inhibition of complex III.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This study is to our knowledge the first to report such data in paired biopsies from human heart, and the results are in agreement with previous observations of decreased OXPHOS capacity in chronic cardiac ischemia in animal models (4,12,16,17). The composition of the present substrate-inhibitor protocol was done with a stepwise addition of substrates: first for complex I linked respiration and then for combined complex-I and -II respiration, followed by inhibition of complex I, leaving only complex II-linked respiration, and finally inhibition of the entire respiratory chain respiration by antimycin A inhibition of complex III.…”
Section: Discussionsupporting
confidence: 92%
“…However, one study reported a preserved OXPHOS capacity but decreased respiratory control ratio (RCR) interpreted as mild uncoupling of the mitochondria (21). Chronic ischemia is thought to produce regions of viable "hibernating" cardiac myocytes with the potential to regain some degree of mitochondrial and contractile function upon reestablishment of sufficient oxygen provision, i.e., via coronary angioplasty bypass grafting (17). In two of the animal studies mentioned above, a protective "chronic preconditioning effect" was reported.…”
mentioning
confidence: 99%
“…It is conceivable that mitochondrial measurements under basal conditions do not represent in vivo conditions at higher work states, which might unmask a propensity for a state of energetic failure. We have observed that within hibernating hearts, contractile reserve in response to a catecholamine infusion remains submaximal, despite successful revascularization with a left internal mammary graft and the inability to enhance oxygen consumption maximally may relate to the observed reduction in key ETC proteins [26]. Several lines of evidence suggest that the mitochondrial proteome retains plasticity with strategies that might improve heart failure, as supported by an observed increase in the expression of mitochondrial ETC proteins following resynchronization of dogs with heart failure [27].…”
Section: Discussionmentioning
confidence: 94%
“…Although somewhat controversial [54], the study results suggest that more novel therapies other than revascularization need to be considered in order to improve contractile function and reduce heart failure. In our swine model of hibernating myocardium hibernation, we subjected the pigs to off-pump revascularization with a LIMA graft and at 4-weeks post-CABG showed that the increase in regional blood flow in response to high-dose infusion of catecholamine was sub-maximal, despite the presence of a widely patent graft [55]. In addition, the mitochondrial proteome remains abnormal at this time, as manifested by reduced expression of electron transport proteins and increased uncoupling protein-2 [56].…”
Section: Management Of Patients With Hibernating Hearts and Ischemic mentioning
confidence: 99%